2014
DOI: 10.1021/am505571m
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis and Characterization of Polyaniline Nanofiber/Silver Nanoparticle Composite Networks as Antibacterial Agents

Abstract: Through a facile and effective seeding polymerization reaction via a one-step redox/complexation process, which took place in aqueous medium at ambient temperature, silver nanoparticles (Ag NPs) embedded polyaniline nanofiber (PANI NF) networks were synthesized as antibacterial agents. During the reaction, not only NF morphology formation of the resulting conducting polymers (CPs) but also amplification of the aqueous silver nitrate (AgNO3) solutions' oxidative potentials were managed by vanadium pentoxide (V2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 57 publications
(337 reference statements)
2
63
2
Order By: Relevance
“…The presence of PANI has been reported to confer anti‐microbial properties to the scaffold . However, this effect was not observed here.…”
Section: Resultscontrasting
confidence: 57%
“…The presence of PANI has been reported to confer anti‐microbial properties to the scaffold . However, this effect was not observed here.…”
Section: Resultscontrasting
confidence: 57%
“…[177][178][179][180][181][182][183] Recently, Polyaniline Nanofibre/ Silver Nanoparticle Composite Networks were prepared via well-known seeding polymerisation method with reported electrical conductivities in the range of 210 −3 to 0.196 Scm -1 applied as an antibacterial agent. 184 Melt spinning is another method that has been used for making composite PAni fibres. However, the use of this method has been restricted because of several issues mentioned earlier, such as relatively low decomposition temperatures, poor control over the exact temperature of the polymer melt during spinning, thermomechanical history of the melt and final fibre structure.…”
Section: -175mentioning
confidence: 99%
“…This approach can Non-enzymatic glucose sensors [109] simultaneously control the morphologies of both conducting polymers and noble metal, without the assistance of other templates or capping agents [108]. For CP/metal network, Zhang et al [109,110] first demonstrated a facile and one-step approach to develop PPy/noble metal nanocomposites starting from the monomer and noble metal salts. This method can be used to synthesize other CPs network deposited with noble metal nanoparticles which can be converted to nanocarbon/noble metal nanocomposites by rapid microwave heating.…”
Section: Strategies To Fabricate Advanced Functional Nanocompositesmentioning
confidence: 99%